Comparative Study on Experimental and Kerner Model Predictions of Viscoelastic Properties of Polyamide 6/ Polyvinyl Alcohol Blends - Pradeepa, K.G.; Shashidhara, G.M. (Journal of Research Updates in Polymer Science, 2018)
The Polyamide 6 (PA6) / Polyvinyl alcohol (PVOH) blends of different compositions (80/20, 60/40 and 50/50) were prepared by melt mixing in a Haake Rheomixer. The selected blend systems (80/20 and 60/40) were modified with dicumyl peroxide (DCP) and tertiary butyl cumyl peroxide (TBCP). The dynamic mechanical properties of blends were systematically investigated with special reference to the effect of blend ratio and effect of presence of peroxide over a temperature range -20°C to 110°C. The effect of change in the composition of the polymer blends on tan δ was studied to understand the damping characteristics. The mean field theory developed by Kerner has been used to estimate the dynamic properties and the estimated values are compared with the experimental values. The loss tangent curve of the blend exhibited single transition peak corresponding to the glass transition temperature (Tg) of Polyamide 6. Kerner model was found to satisfactorily predict the viscoelastic properties of the blends with polyamide content in the range 50 to 80 wt% assuming PA6 as matrix and for all compositions except 80/20 assuming PVOH as matrix. The Kerner model predictions for the selected blend systems with peroxides are not satisfactory and the co-continuous morphology of the peroxide treated blends were revealed by SEM observations.